Hydrophilizing agents for elastomers
A copolymer-based hydrophilizing agent addresses the limitations of existing agents by providing excellent heat resistance, long-term stability, and improved dye dispersibility for elastomers, effectively enhancing their hydrophilic properties.
Patent Information
- Application Number
- JP2020207713
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-12-15
AI Technical Summary
Existing hydrophilizing agents for elastomers face challenges with heat resistance, stability over time, and dye dispersibility, particularly when subjected to high temperature processes like vulcanization.
A hydrophilizing agent comprising a copolymer made from an epoxy group-containing monomer and an alkyl (meth)acrylic acid ester, with specific molecular weight and composition ratios, which imparts hydrophilicity, heat resistance, and stability to elastomers.
The proposed hydrophilizing agent achieves high heat resistance, maintains hydrophilicity over time, and enhances dye dispersibility, making it suitable for various elastomer applications.
Smart Images

Figure 0007665973000001 
Figure 0007665973000002 
Figure 0007665973000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrophilizing agent, and in particular to a hydrophilizing agent which has an effect of imparting hydrophilicity to elastomers and is excellent in heat resistance and stability of hydrophilicity over time. [Background technology]
[0002] Elastomers have excellent heat resistance, abrasion resistance, and elasticity, and are therefore used in a wide range of applications, including everyday items, construction and civil engineering materials, electrical appliance parts, and automobile parts. It is common for elastomers to be modified to meet the required characteristics for each application.
[0003] One of the modifications of elastomers is hydrophilization treatment. By hydrophilizing an elastomer, the surface and inside of the elastomer can be modified. The effects of surface modification include improved wettability, improved adhesion, imparting anti-fogging performance, imparting anti-soiling performance, etc. Furthermore, the effects of internal modification include improved dispersibility of pigments, etc. For example, Patent Document 1 discloses a composition in which a pigment is dispersed inside an elastomer.
[0004] One of the hydrophilization methods is a treatment by plasma irradiation or ultraviolet irradiation. Patent Document 2 discloses a method of hydrophilizing the surface of an ethylene propylene elastomer by irradiating it with plasma or ultraviolet light.
[0005] Another known hydrophilization method is to add a hydrophilizing agent to an elastomer. Patent Document 3 discloses that a rubber composition having excellent hydrophilicity and antifouling properties can be obtained by adding a polyethylene glycol ester as a hydrophilizing agent to an acrylonitrile butadiene elastomer. Patent Document 4 discloses a hydrophilizing agent that is an ester of an alkylene oxide adduct and a monocarboxylic acid having 1 to 24 carbon atoms. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2010-043401 A [Patent Document 2] JP 2013-123975 A [Patent Document 3] JP 2018-53160 A [Patent Document 4] JP 2017-171815 A Summary of the Invention [Problem to be solved by the invention]
[0007] The hydrophilization method using plasma or ultraviolet light disclosed in Patent Document 2 requires an irradiation device in the manufacturing facility, and is therefore unsuitable for application to large products or products with complex shapes.
[0008] On the other hand, in the hydrophilization method using a hydrophilizing agent, if the hydrophilizing agent has low heat resistance, the hydrophilizing agent may decompose and lose its function if the manufacturing process of the product using the elastomer includes a process in which heating is performed (for example, a vulcanization process or a melt-kneading process). The hydrophilizing agent disclosed in Patent Document 4 has a problem in that it is easily thermally decomposed under high temperature conditions. The hydrophilizing agent described in Patent Document 3 can be said to have heat resistance in that it exhibits hydrophilicity even after a vulcanization process. However, Patent Document 3 did not consider changes in properties such as a decrease in hydrophilicity over time. For this reason, there was an issue with the stability of the effect of the hydrophilizing agent over time. Moreover, in neither Patent Document 3 nor Patent Document 4 was evaluation carried out from the viewpoint of dispersibility of the dye.
[0009] An object of the present invention is to provide a hydrophilizing agent which is excellent in heat resistance, has an effect of imparting hydrophilicity to elastomers, and further has excellent stability over time and dispersibility of dyes. [Means for solving the problem]
[0010] As a result of intensive research, the present inventors have found that the above problems can be solved by using a polymer having a specific structure as a hydrophilizing agent. <1> ~ <6> to provide. <1> A hydrophilizing agent comprising a copolymer obtained by polymerizing a monomer component containing an epoxy group-containing monomer (A1) and a (meth)acrylic acid alkyl ester (A2) represented by the following general formula (1), wherein the proportion of the epoxy group-containing monomer (A1) in the monomer component is 10 to 95 mol %, and the proportion of the (meth)acrylic acid alkyl ester (A2) is 5 to 90 mol %. [ka] (In formula (1), R1 represents a hydrogen atom or a methyl group, and R2 represents an alkyl group having 9 to 22 carbon atoms.) <2> The epoxy group-containing monomer (A1) is glycidyl (meth)acrylate. <1> The hydrophilizing agent according to claim 1. <3> The monomer component further contains a hydroxyl group-containing monomer (A3). <1> or <2> The hydrophilizing agent according to claim 1. <4> the proportion of the hydroxyl group-containing monomer (A3) is 60 mol % or less; <3> The hydrophilizing agent according to claim 1. <5> The hydroxyl group-containing monomer (A3) is glycerin mono(meth)acrylate or 2-hydroxyethyl(meth)acrylate. <3> or <4> The hydrophilizing agent according to claim 1. <6> The copolymer has a weight average molecular weight in terms of polystyrene of 3,000 to 50,000. <1> ~ <5> 2. The hydrophilizing agent according to any one of claims 1 to 11. Effect of the Invention
[0011] By using the hydrophilizing agent of the present invention, it is possible to obtain a hydrophilizing agent that has high heat resistance and can impart hydrophilicity to an elastomer. Furthermore, by using the hydrophilizing agent of the present invention, it is possible to obtain an elastomer composition that has excellent stability of hydrophilicity over time and high dispersibility of dyes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The hydrophilizing agent of the present invention will be described in detail below. In this specification, the expression "AA to BB" as a numerical range means "not less than AA and not more than BB".
[0013] [Hydrophilic agent (copolymer P)] The hydrophilizing agent of the present invention is obtained by polymerizing a monomer component containing an epoxy group-containing monomer (A1) and a (meth)acrylic acid alkyl ester (A2) represented by the following general formula (1), and contains a copolymer in which the proportion of the epoxy group-containing monomer (A1) in the monomer component is 10 to 95 mol % and the proportion of the (meth)acrylic acid alkyl ester (A2) is 5 to 90 mol %. [ka] (In general formula (1), R1 represents a hydrogen atom or a methyl group, and R2 represents an alkyl group having 9 to 22 carbon atoms.) In the present invention, the term "(meth)acrylate" is a general term including acrylate and methacrylate.
[0014] The copolymer (P) in the present invention may be composed only of structural units derived from the epoxy group-containing monomer (A1) and the (meth)acrylic acid alkyl ester (A2), or may contain structural units derived from other monomers in addition to the structural units derived from these monomers.
[0015] The copolymer (P) may be in any form, such as a random copolymer, a block copolymer, an alternating copolymer, etc. In particular, a random copolymer is preferred.
[0016] The hydrophilizing agent of the present invention may contain other components in addition to the copolymer (P). The content of the copolymer (P) in the hydrophilizing agent of the present invention is preferably 70 to 100 mass %, more preferably 80 to 100 mass %.
[0017] <Epoxy group-containing monomer (A1)> The copolymer (P) contains a structural unit derived from the epoxy group-containing monomer (A1). By containing the epoxy group-containing monomer as a monomer component, the copolymer (P) can be imparted with hydrophilicity to the elastomer.
[0018] The epoxy group-containing monomer (A1) preferably has a functional group polymerizable with the (meth)acrylic acid alkyl ester (A2). Examples of such functional groups include an acrylic group, a methacrylic group, and a vinyl group. In the present invention, it is particularly preferable that the epoxy group-containing monomer (A1) has an acrylic group or a methacrylic group.
[0019] The epoxy group-containing monomer (A1) is preferably a monomer having a molecular weight of 50 to 500, and more preferably 100 to 300. By using a monomer having the above molecular weight, hydrophilicity can be imparted to the elastomer.
[0020] Examples of the epoxy group-containing monomer (A1) include glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, etc. In view of the effect of imparting hydrophilicity to the elastomer and ease of availability, the epoxy group-containing monomer (A1) is preferably glycidyl (meth)acrylate or 3,4-epoxycyclohexylmethyl (meth)acrylate, and more preferably glycidyl (meth)acrylate. The epoxy group-containing monomer (A1) may be used alone or in combination of two or more. When using two or more, (meth)acrylates having different main chains may be combined, or a methacrylate and an acrylate having the same main chain may be combined.
[0021] In the monomer components of the copolymer (P), the ratio of the epoxy group-containing monomer (A1) (the content ratio of the epoxy group-containing monomer (A1) to the total monomers) is 10 to 95 mol%. If the content ratio of the epoxy group-containing monomer (A1) is less than 10 mol%, the hydrophilicity and pigment dispersibility of the elastomer are reduced. On the other hand, if the content ratio of the epoxy group-containing monomer (A1) exceeds 95 mol%, it becomes difficult to exhibit hydrophilicity and the stability over time is reduced. From the viewpoint of imparting appropriate hydrophilicity to the elastomer, the content ratio of the epoxy group-containing monomer (A1) is preferably 15 to 50 mol%, more preferably 20 to 40 mol%.
[0022] <(Meth)acrylic acid alkyl ester (A2)> The copolymer (P) contains a structural unit derived from the (meth)acrylic acid alkyl ester (A2). When the copolymer (P) contains the (meth)acrylic acid alkyl ester (A2) as a monomer component, the stability over time of the hydrophilizing agent and the dispersibility of the dye can be improved. The (meth)acrylic acid alkyl ester (A2) in the present invention is represented by the following general formula (1). [ka] In the general formula (1), R1 is a hydrogen atom or a methyl group, preferably a methyl group from the viewpoint of polymerizability. R2 is an alkyl group having 9 to 22 carbon atoms. Examples of the alkyl group having 9 to 22 carbon atoms include a nonyl group, a decyl group, a dodecyl group, a lauryl group, and a stearyl group. From the viewpoint of imparting hydrophilicity to the elastomer, the number of carbon atoms in the alkyl group constituting R2 is preferably 12 to 22. Furthermore, from the viewpoint of the heat resistance and stability over time of the hydrophilizing agent, the number of carbon atoms in the alkyl group constituting R2 is more preferably 16 to 18, and particularly preferably 18. R2 may be a branched alkyl group or a linear alkyl group, but is particularly preferably a linear alkyl group. When R2 is a branched alkyl group, the main chain of R2 preferably has 9 or more carbon atoms.
[0023] Examples of the (meth)acrylic acid alkyl ester (A2) applicable to the present invention include stearyl (meth)acrylate, lauryl (meth)acrylate, behenyl (meth)acrylate, etc. Among these, stearyl (meth)acrylate is preferred, and stearyl methacrylate is particularly preferred.
[0024] The (meth)acrylic acid alkyl ester (A2) may be used alone or in combination of two or more kinds.
[0025] In the monomer components of the copolymer (P), the proportion of the (meth)acrylic acid alkyl ester (A2) (the content of the (meth)acrylic acid alkyl ester (A2) relative to the total monomers) is 5 to 90 mol %. If the content of the (meth)acrylic acid alkyl ester (A2) is less than 5 mol %, it is difficult to impart hydrophilicity, heat resistance, and stability over time to the elastomer. On the other hand, if the content of the (meth)acrylic acid alkyl ester (A2) is more than 90 mol %, the pigment dispersibility and hardness of the elastomer may decrease. In consideration of hydrophilicity, heat resistance, stability over time, and pigment dispersibility, the content of the (meth)acrylic acid alkyl ester (A2) is more preferably 7 to 50 mol %, and even more preferably 10 to 30 mol %.
[0026] The ratio of the content of the (meth)acrylic acid alkyl ester (A2) to the total content of the epoxy group-containing monomer (A1) and the (meth)acrylic acid alkyl ester (A2) is preferably 0.30 to 0.70, more preferably 0.30 to 0.65, and particularly preferably 0.30 to 0.60. By increasing the content of the (meth)acrylic acid alkyl ester (A2) within the above range, it is possible to obtain a copolymer (P) that can be made into an elastomer having good hydrophilicity, heat resistance, stability over time, and pigment dispersion.
[0027] <Hydroxyl-containing monomer (A3)> The copolymer (P) may further contain a structural unit derived from a hydroxyl-containing monomer (A3). By containing the hydroxyl-containing monomer (A3) as a monomer component in the copolymer (P), the hydrophilicity and pigment dispersibility of the elastomer can be further improved, and the elastomer can have an appropriate hardness.
[0028] The hydroxyl-containing monomer (A3) preferably has a functional group polymerizable with the (meth)acrylic acid alkyl ester (A2). Examples of such functional groups include an acrylic group, a methacrylic group, and a vinyl group. In the present invention, the hydroxyl-containing monomer (A3) particularly preferably has an acrylic group or a methacrylic group.
[0029] The hydroxyl group-containing monomer (A3) is preferably a monomer having a molecular weight of 50 to 1000, and more preferably 100 to 300. By using a monomer having the above molecular weight, it is possible to impart appropriate hydrophilicity, pigment dispersibility and hardness to the elastomer.
[0030] Examples of the hydroxyl group-containing monomer (A3) include glycerin mono(meth)acrylate, 2-hydroxyethyl(meth)acrylate, hydroxypropyl(meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, hydroxyphenyl(meth)acrylate, etc. From the viewpoints of compatibility with elastomers and hydrophilicity-imparting effect, glycerin mono(meth)acrylate and 2-hydroxyethyl(meth)acrylate are preferred, 2-hydroxyethyl(meth)acrylate is more preferred, and 2-hydroxyethyl(meth)acrylate is particularly preferred.
[0031] In the monomer components of the copolymer (P), the proportion of the hydroxyl-containing monomer (A3) (the content of the hydroxyl-containing monomer (A3) relative to all monomers) is preferably 60 mol% or less. By making the proportion of the hydroxyl-containing monomer (A3) 60 mol% or less, an elastomer having good hydrophilicity, pigment dispersibility and hardness can be obtained. The proportion of the hydroxyl-containing monomer (A3) is more preferably 55 mol% or less, and even more preferably 50 mol% or less. From the viewpoint of obtaining the above-mentioned effects of the hydroxyl-containing monomer (A3), the proportion of the hydroxyl-containing monomer (A3) is preferably 20 mol% or more, and more preferably 30 mol% or more.
[0032] The ratio (molar ratio) of the content of the hydroxyl-containing monomer (A3) to the total content of the epoxy-containing monomer (A1) and the hydroxyl-containing monomer (A3) is preferably 0.30 to 0.80, more preferably 0.40 to 0.70. The ratio (molar ratio) of the content of the hydroxyl-containing monomer (A3) to the total content of the (meth)acrylic acid alkyl ester (A2) and the hydroxyl-containing monomer (A3) is preferably 0.40 to 0.80, more preferably 0.50 to 0.70. By setting it within the above range, it is possible to obtain a copolymer (P) that can be made into an elastomer having good hydrophilicity, pigment dispersibility and hardness.
[0033] <Other Monomers> The copolymer (P) may contain, in addition to the structural units derived from the above (A1) to (A3), structural units derived from monomers polymerizable with (A1) to (A3). By incorporating other monomer components into the copolymer (P), various physical properties of the hydrophilizing agent can be adjusted. Examples of the other monomers include alkyl (meth)acrylates having 1 to 8 carbon atoms. Examples of the alkyl groups having 1 to 8 carbon atoms include methyl, ethyl, butyl, and octyl groups. In this case, the ratio of other monomers in the monomer components of the copolymer (P) (the ratio of monomers other than A1 to A3 to the total monomers) is preferably 30 mol % or less, more preferably 15 mol % or less, and even more preferably 10 mol % or less, from the viewpoint of obtaining the effects of the above monomer components (A1) to (A3).
[0034] <Molecular weight of copolymer (P)> The copolymer (P) of the present invention has a weight average molecular weight (Mw) in terms of polystyrene of preferably 3,000 to 50,000, more preferably 4,000 to 30,000, and even more preferably 5,000 to 15,000. By making the Mw of the copolymer (P) 3,000 or more, it is possible to ensure stability over time when added to an elastomer. In addition, by making the Mw of the copolymer (P) 50,000 or less, it is possible to improve the compatibility between the elastomer and the copolymer (P).
[0035] The copolymer (P) of the present invention has a polydispersity [Mw / Mn (weight average molecular weight / number average molecular weight)] of preferably 1.5 to 4.0, more preferably 1.5 to 2.5. By setting the polydispersity of the copolymer (P) within the above range, the above-mentioned effects of the present invention can be imparted in a well-balanced manner.
[0036] The weight average molecular weight (Mw), number average molecular weight (Mn) and dispersity (Mw / Mn) of the copolymer (P) are determined by gel permeation chromatography (GPC) using polystyrene as a standard substance.
[0037] [Production method of copolymer (P)] Next, the method for producing the copolymer (P) of the present invention will be described. The copolymer (P) can be obtained by radical polymerization of a monomer mixture containing at least an epoxy group-containing monomer (A1), an (meth)acrylic acid alkyl ester (A2), and a hydroxyl group-containing monomer (A3). The polymerization can be carried out by a known method, such as solution polymerization, suspension polymerization, emulsion polymerization, etc. Solution polymerization or suspension polymerization is preferred in that the weight average molecular weight (Mw), number average molecular weight (Mn), and dispersity (Mw / Mn) of the copolymer (P) can be easily adjusted within the above ranges.
[0038] As the polymerization initiator, a known one can be used. For example, organic peroxides such as 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, and azo-based polymerization initiators such as 2,2'-azobisisobutyronitrile can be used. The polymerization initiator may be used alone or in combination of two or more kinds. The amount of the polymerization initiator used can be appropriately set depending on the combination of monomers used, reaction conditions, and the like. The polymerization initiator may be added all at once, or a part of it may be added all at once and the rest may be added dropwise, or the entire amount may be added dropwise. It is preferable to add the polymerization initiator dropwise together with the monomer mixture, since this makes it easier to control the reaction. Furthermore, it is preferable to add the polymerization initiator after the monomer mixture is added dropwise, since this can reduce the amount of residual monomers.
[0039] The polymerization solvent used in the solution polymerization can be one in which the monomer and the polymerization initiator are soluble, such as methanol, ethanol, 1-propanol, acetone, methyl ethyl ketone, and propylene glycol monomethyl ether. The concentration of the monomer mixture relative to the polymerization solvent is preferably 10 to 60% by mass, more preferably 20 to 50% by mass. If the concentration of the monomer mixture is too low, the monomers tend to remain after the reaction, and the molecular weight of the resulting copolymer may decrease. On the other hand, if the concentration of the monomers is too high, it may become difficult to control heat generation. When the monomer is added to the polymerization solvent, the entire amount may be added at once, or a part of the monomer may be added at once and the rest may be added dropwise, or the entire amount may be added dropwise. From the viewpoint of ease of controlling heat generation, it is preferable to add a part of the monomer at once and the rest may be added dropwise, or to add the entire amount dropwise.
[0040] The polymerization temperature can be appropriately set depending on the type of polymerization solvent, etc., but is preferably within the range of 50° C. to 110° C. The polymerization time can be set depending on the type of polymerization initiator and the polymerization temperature. For example, when 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate is used as the polymerization initiator, the polymerization temperature is set to 90° C., and the polymerization time is suitably about 6 hours.
[0041] By carrying out the above polymerization reaction, copolymer (P), which is an active ingredient of the hydrophilizing agent of the present invention, can be obtained. The obtained copolymer (P) may be used as it is, or may be isolated by removing the solvent, filtering or purifying the reaction solution after the polymerization reaction.
[0042] [Elastomer composition] When the copolymer (P) of the present invention is prepared into an elastomer composition, it is suitably used as a hydrophilizing agent for the elastomer. The above-mentioned elastomers include thermosetting elastomers and thermoplastic elastomers. Examples of the thermosetting elastomers include diene-based rubbers such as natural rubber, isoprene rubber, butadiene rubber, and styrene-butadiene rubber; non-diene rubbers such as urethane rubber, silicone rubber, and fluororubber; and the like. Examples of the thermoplastic elastomers include polystyrene-based elastomers such as polystyrene and styrene-butadiene elastomers, olefin / alkene-based elastomers such as polyethylene and ethylene-vinyl acetate elastomers, and polyvinyl chloride-based elastomers.
[0043] When the polymer (P) of the present invention is present in the thermosetting elastomer, it is preferable to mix the rubber composition before vulcanization with the copolymer (P) and then vulcanize the mixture.
[0044] The content of the copolymer (P) of the present invention in the elastomer composition is preferably 0.5 parts by mass to 30 parts by mass, more preferably 1 part by mass to 20 parts by mass, and even more preferably 2 parts by mass to 10 parts by mass, when the mass of the elastomer is 100 parts by mass. By setting the content of the copolymer within the above range, it is possible to appropriately impart hydrophilicity to the elastomer.
[0045] The elastomer composition may contain various components that are generally added to adjust physical properties, as necessary. Examples of such components include plasticizers, crosslinking agents, softeners, tackifiers, antistatic agents, fillers, antioxidants, silane coupling agents, zinc oxide, vulcanization accelerators, vulcanizing agents, stearic acid, workability improvers, resins, waxes, oils, and solvents, which may be appropriately selected and contained within a range that does not impair the object of the present invention.
[0046] The elastomer composition can be produced by blending the above-mentioned components and kneading them by a known method. EXAMPLES
[0047] The present invention will now be described more specifically with reference to examples and comparative examples. [Polymerization of copolymer (P)] Copolymers P1 to P7 and comparative copolymers P'1 to P'3 were obtained according to the following polymerization examples. The proportion of monomer components in each copolymer is shown in Table 1. In Table 1, the proportion of monomer components is in mol %.
[0048] (Polymerization Example 1) A 1 L separable flask (reaction vessel) equipped with a stirrer, a thermometer, a condenser, a dropping funnel, and a nitrogen inlet tube was charged with 210.0 g of methyl ethyl ketone (product name: MEK, manufactured by Maruzen Petrochemical Co., Ltd.), and the atmosphere in the flask was replaced with nitrogen to create a nitrogen atmosphere. A monomer solution was prepared by mixing 50.0 g of glycidyl methacrylate (product name: Blenmer G, manufactured by NOF Corp., described as "GMA" in Table 1), 80.0 g of stearyl methacrylate (product name: Blenmer SMA, manufactured by NOF Corp., described as "SMA" in Table 1), 70.0 g of 2-hydroxyethyl methacrylate (product name: Blenmer E, manufactured by NOF Corp., described as "HEMA" in Table 1), and 40.0 g of methyl ethyl ketone. Also, a polymerization initiator solution was prepared by mixing 50.0 g of t-butyl peroxyneodecanoate (product name: Perbutyl ND, manufactured by NOF Corporation) and 50.0 g of methyl ethyl ketone. The temperature inside the reaction vessel was raised to 75° C., and the monomer solution and the polymerization initiator solution were simultaneously dropped over two hours, respectively, and then the reaction was carried out for three hours at 75° C. After the reaction was completed, methyl ethyl ketone was distilled off to obtain a copolymer P1.
[0049] (Polymerization Example 2) A copolymer P2 was obtained in the same manner as in Polymerization Example 1, except that the monomers were changed to 30.0 g of glycidyl methacrylate, 120.0 g of stearyl methacrylate, and 50.0 g of 2-hydroxyethyl methacrylate.
[0050] (Polymerization Example 3) Copolymer P3 was obtained in the same manner as in Polymerization Example 1, except that the monomers were changed to 50.0 g of glycidyl methacrylate, 80.0 g of lauryl methacrylate (product name: Blenmer LMA, manufactured by NOF Corporation, referred to as "LMA" in Table 1), and 70.0 g of 2-hydroxyethyl methacrylate.
[0051] (Polymerization Example 4) Copolymer P4 was obtained in the same manner as in Polymerization Example 1, except that the monomers were changed to 50.0 g of glycidyl methacrylate, 80.0 g of stearyl methacrylate, and 70.0 g of glycerin monomethacrylate (product name: Blenmer GLM, manufactured by NOF Corporation; referred to as "GLM" in Table 1).
[0052] (Polymerization Example 5) Polymer P5 was obtained in the same manner as in Polymerization Example 1, except that the monomers were changed to 50.0 g of glycidyl methacrylate, 70.0 g of stearyl methacrylate, 70.0 g of 2-hydroxyethyl methacrylate, and 10.0 g of methyl methacrylate (product name: MMA monomer, manufactured by Kuraray Co., Ltd., referred to as "MMA" in Table 1).
[0053] (Polymerization Example 6) Copolymer P6 was obtained in the same manner as in Polymerization Example 1, except that the monomers were changed to 80.0 g of glycidyl methacrylate, 50.0 g of stearyl methacrylate, and 70.0 g of 2-hydroxyethyl methacrylate.
[0054] (Polymerization Example 7) Copolymer P7 was obtained in the same manner as in Polymerization Example 1, except that the monomers were changed to 40.0 g of glycidyl methacrylate and 160.0 g of stearyl methacrylate.
[0055] (Polymerization Example 8) Comparative copolymer P'1 was obtained in the same manner as in Polymerization Example 1, except that the monomers were changed to 50.0 g of glycidyl methacrylate, 70.0 g of 2-hydroxyethyl methacrylate, and 80.0 g of methyl methacrylate.
[0056] (Polymerization Example 9) Comparative copolymer P'2 was obtained in the same manner as in Polymerization Example 1, except that the monomer was changed to 200.0 g of glycidyl methacrylate.
[0057] (Polymerization Example 10) Comparative copolymer P'3 was obtained in the same manner as in Polymerization Example 1, except that the monomer was changed to 200.0 g of 2-hydroxyethyl methacrylate.
[0058] [Measurement of weight average molecular weight and dispersity of copolymer] The weight average molecular weight (Mw) and number average molecular weight (Mn) of copolymers P1 to P7 and P'1 to P'3 were measured by gel permeation chromatography (GPC) under the following conditions. Table 1 shows the weight average molecular weight (Mw) and dispersity (Mw / Mn). Equipment: Tosoh Corporation, HLC-8220 Column: Shodex, LF-804 Standard material: polystyrene Eluent: THF (tetrahydrofuran) Flow rate: 1.0ml / min Column temperature: 40℃ Detector: RI (Differential Refractive Index Detector)
[0059] [Table 1]
[0060] [Preparation of elastomer composition] Example 1 、3 ~ 6, 8, Reference examples 1-2 , Comparative Examples 1 to 3) 0.5 g of each of the copolymers P1 to P7 and P'1 to P'3 was weighed out and mixed with 10 g of an olefin / alkene-based elastomer (product name: Ultrathene 685, manufactured by Tosoh Corporation) and 39.5 g of toluene to prepare Example 1. 、3 ~ 6, 8, Reference examples 1-2 And toluene solutions of the elastomer compositions of Comparative Examples 1 to 3 were prepared.
[0061] Example 8 3.0 g of copolymer P2 was weighed out, and mixed with 10 g of ethylene propylene elastomer (product name: EP912, manufactured by JSR Corporation) and 39.5 g of toluene to prepare a toluene solution of the elastomer composition of Example 8.
[0062] (Reference example) A polyoxyethylene alkyl ether (product name: Nonion E-202S, manufactured by NOF Corporation) was used as a hydrophilizing agent and mixed with an olefin / alkene-based elastomer and toluene in the same manner as in Example 1 to prepare a toluene solution of the elastomer composition of the reference example.
[0063] The compounding ratios of the hydrophilizing agent and the elastomer for each of the Examples, Comparative Examples, and Reference Examples are shown in Table 2. The amount of each component in Table 2 is in "parts by mass."
[0064] [evaluation] (1) Evaluation of hydrophilicity (initial hydrophilicity) Example 1 、3 ~ 6, 8, Reference examples 1-2 The toluene solutions of the elastomer compositions of Comparative Examples 1 to 3 and Reference Example were each applied onto a glass substrate using a bar coater, and then dried on a hot plate at 100° C. for 30 minutes, thereby forming a resin film with a thickness of 1 μm. The contact angle of the obtained resin film was measured by the tangent method in accordance with JIS R3257. The hydrophilicity of the resin film was evaluated according to the following indices. The evaluation results and the contact angle are shown in Table 2. A (very good hydrophilicity): Contact angle less than 30° B (good hydrophilicity): Contact angle is 30° or more and less than 45° C (slightly poor hydrophilicity): Contact angle is 45° or more but less than 75° D (poor hydrophilicity): Contact angle is 75° or more
[0065] (2) Heat resistance evaluation Example 1 、3 ~ 6, 8, Reference Examples 1-210 g of each of the toluene solutions of the elastomer compositions of Comparative Examples 1 to 3 and Reference Example was weighed out and dried in a vacuum drying oven at 120°C and -0.1 kPa or less for 1 hour to prepare a sample. 10 mg of the obtained sample was placed in an aluminum pan and heated to 300°C at a rate of 10°C / min in an air atmosphere using a thermogravimetric analyzer (STA7200, Hitachi High-Eco Science Co., Ltd.) to measure the thermal weight loss rate. The heat resistance of the copolymer (hydrophilizing agent) was evaluated using the temperature (Td5) at which the thermal weight loss rate reached 5% according to the following index. The evaluation results and Td5 values are shown in Table 2. A (very good heat resistance): Td5 is 270℃ or higher B (good hydrophilicity): Td5 is 250°C or higher and less than 270°C C (slightly poor hydrophilicity): Td5 is 240°C or higher but less than 250°C D (poor hydrophilicity): Td5 is less than 240°C
[0066] (3) Evaluation of stability over time The glass substrate with the resin film formed thereon obtained in (1) was stored at 80°C and 70% humidity for one week. The resin film was then washed with water and dried at room temperature for one day. The contact angle of the dried resin film (contact angle over time) was measured in the same manner as in (1). The rate of change in the contact angle was calculated using the contact angle (initial contact angle) measured in (1) as a reference according to the following formula. Rate of change (%) = |(initial contact angle) - (contact angle over time)| / (initial contact angle) x 100 The stability of the resin film was evaluated according to the following indices. The evaluation results and the rate of change are shown in Table 2. A (very good stability): Change rate is 3.0% or less B (Good stability): Change rate is greater than 3.0% and less than 5.0% C (slightly poor stability): Change rate is 5.0% or more but less than 10.0% D (poor stability): Change rate is 10.0% or more
[0067] (4) Evaluation of pigment dispersion Example 1 、3 ~ 6, 8, Reference Examples 1-20.1 g of Green No. 3 was added as a dye to 50 g of a toluene solution of the elastomer compositions of Comparative Examples 1 to 3 and Reference Example, and mixed for 60 minutes. The dye-containing elastomer composition was applied onto a glass substrate with a bar coater, and dried on a hot plate at 100°C for 30 minutes. This formed a resin film with a thickness of 1 μm. The obtained resin film was observed with an optical microscope (magnification: 10 times) and visually. The dispersibility of the pigment was evaluated according to the following indices. The results are shown in Table 2. A (good dispersibility): When observed under a microscope, the coating film was uniform and free of unevenness, and the surface was evaluated to be almost smooth. B (slightly good dispersibility): Unevenness was observed under a microscope, but not with the naked eye. C (poor dispersibility): Unevenness and roughness can be visually confirmed
[0068] [Table 2]
[0069] As shown in Table 2, the elastomer compositions of Examples 1 to 8 had excellent initial hydrophilicity, and even after storage under high temperature and high humidity conditions, the change in hydrophilicity was small, and excellent stability over time was obtained. Furthermore, the dispersibility of the pigment was also good. Furthermore, the results of the heat resistance evaluation showed that the copolymers P1 to P7 of the present invention had excellent heat resistance. On the other hand, in Comparative Examples 1 to 3, the initial hydrophilicity was insufficient, and the stability over time was also poor. Also, in Comparative Examples 1 to 3, the dispersibility of the dye was poor. The Reference Examples are conventional products having a structure different from that of the Examples, but they do not satisfy all of the requirements for hydrophilicity, heat resistance, stability and pigment dispersibility.
Claims
1. A hydrophilizing agent for elastomers, comprising a copolymer obtained by polymerizing a monomer component including an epoxy group-containing monomer (A1), a (meth)acrylic acid alkyl ester (A2) represented by the following general formula (1), and a hydroxyl group-containing monomer (A3), wherein, in the monomer component, a ratio of the epoxy group-containing monomer (A1) is 15 to 50 mol %, a ratio of the (meth)acrylic acid alkyl ester (A2) is 7 to 50 mol %, and a ratio of the hydroxyl group-containing monomer (A3) is 42.6 to 60 mol %. 【Chemistry 1】 (In formula (1), R1 represents a hydrogen atom or a methyl group, and R2 represents an alkyl group having 9 to 22 carbon atoms.)
2. 2. The hydrophilizing agent for elastomers according to claim 1, wherein the epoxy group-containing monomer (A1) is glycidyl (meth)acrylate.
3. 3. The hydrophilizing agent for elastomers according to claim 1, wherein the hydroxyl group-containing monomer (A3) is glycerin mono(meth)acrylate or 2-hydroxyethyl(meth)acrylate.
4. The hydrophilizing agent for elastomers according to any one of claims 1 to 3, wherein the copolymer has a weight average molecular weight in terms of polystyrene of 3,000 to 50,000.
Citation Information
Patent Citations
Surface modification of polymeric material with graft copolymer
JP1982179246A
Surface modification of polymeric material
JP1989000111A
Coating composition for metal surface
JP1990011673A
Heat-curable antifogging agent composition
JP1991221566A
Coating composition and cured product
JP2002294157A